New Mitogenomes of the Green Lacewing Tribe Ankylopterygini (Neuroptera: Chrysopidae: Chrysopinae) and Phylogenetic Implications of Chrysopidae - Shuo Tian; Yunlan Jiang; Yan Lai; Shutong Wang; Xingyue Liu; Yuyu Wang (Insects, 2023)
Chrysopidae (green lacewings) are a cosmopolitan and species-rich family of Neuroptera, with remarkable significance of biological control against various agricultural and forestry pests. However, the phylogenetic position of Chrysopidae in Neuroptera and the internal relationships within the family remain equivocal among previous studies based on different types of data and sampling. Here we sequenced the mitochondrial genomes (mitogenomes) of two species of the genus Ankylopteryx in the chrysopine tribe Ankylopterygini for the first time. The characteristics of these mitogenomes were analyzed in comparison with other green lacewing mitogenomes published to date. In the phylogeny herein reconstructed based on mitogenomes, Chrysopinae were recovered as the sister group to Apochrysinae + Nothochrysinae. Within the subfamily of Chrysopinae, Nothancylini were recovered as the sister group to (Leucochrysini + Belonopterygini) + (Ankylopterygini + Chrysopini). The divergence time estimation suggested an Early Cretaceous initial divergence within the extant Chrysopidae. Within Chrysopinae, the four tribes except Nothancylini diverged around mid-Cretaceous.